Estudo da liga magnética "Alnico" sintetizado na forma de nanoplacas - Ferreira, Rafael Franco (2016)
Nanostructured Alnico was prepared by a combination of dry and wet high-energy millings of a mixture of Fe, Co, Ni, Al and Cu powders. Rounded pellets were made by compacting the as-milled powder and then submitting it to thermal treatments at different temperatures. The as-milled and as-annealed samples were characterized by X-ray diffractometry, Mössbauer spectroscopy, scanning electron microscopy and magnetization techniques. The as-milled material revealed a face-centered cubic structure and nanoplate morphology, with a high aspect ratio and planar magnetization. The heat treatment transformed the crystalline structure mostly to body centered cubic, which is characteristic of Alnico at room temperature, with a microstructure made of nanoplates overlaid perpendicularly to the compaction direction. They revealed a coercive field and a saturation magnetization lower and higher, respectively, than that of alnico commercial samples .